Cytogenetic analysis of Epicauta atomaria (Meloidae) and Palembus dermestoides (Tenebrionidae) with Xyp sex determination system using standard staining, C-bands, NOR and synaptonemal complex microspreading techniques - Almeida, Mara Cristina de; Zacaro, Adilson Ariza; Cella, Doralice Maria [UNESP] (Springer Nature, 2000)
The mitotic and meiotic chromosomes of the beetles Epicauta atomaria (Meloidae) and Palembus dermestoides (Tenebrionidae) were analysed using standard staining, C-banding and silver impregnation techniques. We determine the diploid and haploid chromosome numbers, the sex determination system and describe the chromosomal morphology, the C-banding pattern and the chromosome(s) bearing NORs (nucleolar organizer regions). Both species shown 2n = 20 chromosomes, the chromosomal meioformula 9 + Xyp, and regular chromosome segregation during anaphases I and II. The chromosomes of E. atomaria are basically metacentric or submetacentric and P. dermestoides chromosomes are submetacentric or subtelocentric. In both beetles the constitutive heterochromatin is located in the pericentromeric region in all autosomes and in the Xp chromosome; additional C-bands were observed in telomeric region of the short arm in some autosomes in P. dermestoides. The yp chromosome did not show typical C-bands in these species. As for the synaptonemal complex, the nucleolar material is associated to the 7th bivalent in E. atomaria and 3rd and 7th bivalents in P. dermestoides. Strong silver impregnated material was observed in association with Xyp in light and electron microscopy preparations in these species and this material was interpreted to be related to nucleolar material.
Keywords: Chromosome; Coleoptera; Heterochromatin; Karyotype; Meiosis; Nucleolus; Pachytene; Polyphag a; anaphase; animal cell; autosome; beetle; centromere; chromosome; chromosome analysis; chromosome banding pattern; chromosome C band; chromosome NOR; chromosome number; chromosome segregation; chromosome structure; chromosome Xp; chromosome Yp; diploidy; haploidy; heterochromatin; karyotype; male; meiosis; mitosis; morphology; nonhuman; pachytene; sex determination; silver impregnation; staining; synaptonemal complex; technique; Animals; Beetles; Cell Nucleus; Chromosome Banding; Female; Karyotyping; Male; Sex Determination (Genetics); Synaptonemal Complex; X Chromosome; Animalia; Epicauta; Epicauta atomaria; Insecta; Meloidae; Palembus; Palembus dermestoides; Tenebrionidae